2015
DOI: 10.1007/s11418-015-0914-8
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase-IV inhibitory activity of dimeric dihydrochalcone glycosides from flowers of Helichrysum arenarium

Abstract: A methanol extract of everlasting flowers of Helichrysum arenarium L. Moench (Asteraceae) was found to inhibit the increase in blood glucose elevation in sucrose-loaded mice at 500 mg/kg p.o. The methanol extract also inhibited the enzymatic activity against dipeptidyl peptidase-IV (DPP-IV, IC50 = 41.2 μg/ml), but did not show intestinal α-glucosidase inhibitory activities. From the extract, three new dimeric dihydrochalcone glycosides, arenariumosides V–VII (2–4), were isolated, and the stereostructures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…An interesting feature of nonpolar DCM and ACN extracts is the presence of (poly)methoxylated flavones, i.e. dimethoxy- (49,53) and pentamethoxyflavones in DCME (46,47) and methoxy-(51, 52), dimethoxy- (50), and triethoxydimethoxy flavones in ACNE (54,55,57). [22] + + + arenol [23] + + + plicatipyrone analog [22] + arzanol [27] + + + heliarzanol [23] + + cycloarzanol [23] + helipyrone diacetate [25] + + methylarzanol [23] + + 3-[1-[3-acetyl-2,4,6-trihydroxy-5-(3-methyl-2-buten-1-yl)phenyl]ethyl]-6-ethyl-4-hydroxy-5-methyl-2H-pyran-2-one [23] + + auricepyrone [22], 23-methyl-6-O-desmethylauricepyrone [22] + helicerastripyrone [28] [29] + plicatipyrone analog [26]…”
Section: Phytochemical Profilementioning
confidence: 99%
See 1 more Smart Citation
“…An interesting feature of nonpolar DCM and ACN extracts is the presence of (poly)methoxylated flavones, i.e. dimethoxy- (49,53) and pentamethoxyflavones in DCME (46,47) and methoxy-(51, 52), dimethoxy- (50), and triethoxydimethoxy flavones in ACNE (54,55,57). [22] + + + arenol [23] + + + plicatipyrone analog [22] + arzanol [27] + + + heliarzanol [23] + + cycloarzanol [23] + helipyrone diacetate [25] + + methylarzanol [23] + + 3-[1-[3-acetyl-2,4,6-trihydroxy-5-(3-methyl-2-buten-1-yl)phenyl]ethyl]-6-ethyl-4-hydroxy-5-methyl-2H-pyran-2-one [23] + + auricepyrone [22], 23-methyl-6-O-desmethylauricepyrone [22] + helicerastripyrone [28] [29] + plicatipyrone analog [26]…”
Section: Phytochemical Profilementioning
confidence: 99%
“…Compound Class/Name EE DCME ACNE helichrysoside [51] + quercetin [40] + + tiliroside [52] + tiliroside analog [52] + kaempferol [41] + chalcone arenariumoside V [53], arenariumoside VI [53], arenariumoside VII [53] + tomoroside A [53] + isosalipurposide [40] + helilupolone [54] + Terpenoid sesquiterpenoid sesquiterpene derivative [55][56][57] + sesquiterpene derivative [55][56][57] + sesquiterpene derivative [58][59][60] + sesquiterpene derivative [61,62] + sesquiterpene derivative [62][63][64] + eudesmane derivative [65] + sesquiterpene derivative [66][67][68] + sesquiterpene derivative [66][67][68] + ainsliaside E [69] + cinnamoyloxy-hydroxyeudesmane [70] + athrolide C [71] + + athrolide D [71] + diterpenoid diterpene derivative [30,72] + 8-(acetyloxy)-3-ethenyloctahydro-10-hydroxy-3,4a,7,7,10a-pentamethyl-1H-naphtho[2,1-b]pyran-2,5(3H,4aH)-dione [72] + (7-ethenyl-1,2,3,4,4a,4b,5,6,7,8,10,10a-dodecahydro-1,4a,7-trimethyl-1-phenanthrenyl)methyl-butanedioic acid methyl ester [72] + ent-kaurane derivative [73] + gymnospermin …”
Section: Nomentioning
confidence: 99%
“…Therefore improving postprandial hyperglycemia may form part of the strategy for the prevention and management of cardiovascular disease in diabetes. 136) We previously reported that several antidiabetogenic therapeutic candidates were obtained from natural resources such as Kochia scoparia, 137) Borassus flabellifer, 138) Solanum lycocarpum, 139) Sinocrassula indica, 140) Shorea roxburghii, 141) Helichrysum arenarium, 142) and Salacia reticulata, S. oblonga, and S. chinensis [143][144][145][146][147][148] evaluated by postprandial hyperglycemia in sugar-loaded rats and/or mice models. In these experiments the effects of the principal phenylethanoid glycosides from the stems of C. tubulosa, echinacoside (28) and acteoside (29), on postprandial increase in blood glucose levels in starch-loaded mice were examined.…”
Section: Glucose Tolerance-improving Activitymentioning
confidence: 99%
“…These findings suggest that an aldose reductase inhibitor may have the capacity of preventing and/or treating several diabetic complications. 153) As potent aldose reductase inhibitors from natural resources, we identified several flavonoids, [154][155][156][157][158][159][160] stilbenoids, 141,154) terpenoids, 161) and quinic acid derivatives. 159) As shown in Table 8, several phenylethanoid glycosides, echinacoside (28, IC 50 = 3.1 µM), acteoside (29, 1.2 µM), kankanoside J 1 (35, 9.3…”
Section: Glucose Tolerance-improving Activitymentioning
confidence: 99%
“…An increase of mitochondrial enzyme activity occurred with extracts of Potentilla anserine L [11]. Three other plants used in VL improve incretin secretion and, hence, insulin synthesis, and show a hypoglycemic activity; Helichrysum arenarium L. Moench [16], Anethum graveolens L [6] and Melissa officinalis [17].…”
Section: Introductionmentioning
confidence: 99%